End of life after stroke: A nationwide study of 42, 502 deaths occurring within a year after stroke. (March 2018) - Asplund, Kjell; Lundström, Staffan; Stegmayr, Birgitta
Introduction: In the scientific literature, there is very limited empirical information on end-of-life issues after stroke in the scientific literature. The present nationwide study describes the circumstances surrounding deaths that occur within a year after a stroke. Patients and methods: Datasets from three nationwide Swedish registers (on stroke, palliative care and cause of death) were linked. Basic information was available for 42, 502 unselected cases of death that occurred within a year after a stroke and more detailed information was available for 16, 408 deaths. Odds ratios for characteristics of end-of-life care were calculated by logistic regression. Results: In the late phase after stroke (three months to one year), 46% of patients died in a nursing home, whereas 37% of patients died in a hospital after readmission and 10% of patients died at home. Eleven per cent of deaths were reported as being unexpected. A next of kin was present at 49% of deaths. The frequency of unattended deaths (neither next of kin nor staff were present at the time of death) ranged from 5% at home with specialised home care to 25% in hospitals. Discussion: This is, by far, the largest study published on end-of-life issues after stroke. Major differences between countries in healthcare, community services, family structure and culture may limit direct transfer of the present results to other settings. Conclusion: There is considerable discordance between presumed 'good death' late after stroke (dying at home surrounded by family members) and the actual circumstances at the end of life.